Arakon and Arab Andalusian Culture: Elsa Crazy as a model - Mnite, Layla (Al-Adab Journal, 2021)
The issue of the influence of Arab Andalusian poetry on modern European poetry is one of the issues that occupied and still preoccupies many researchers, both ancient and modern, because the emergence of many new topics, added every day, confirms this influence. His poem "Majnoun Elissa" is clearly influenced by Andalusian literature, and there is no room for doubt about his truth in literature. This effect appears in the poetic symbols that the poet employed in expressing his poetic meanings and poetic meaning.